Aircraft landing gear extension and retraction control system diagnostics, prognostics and health management - Yang, Yang (Cranfield University, 2012)
This thesis contains the Group Design Project (GDP) work and Individual Research Project (IRP) work. The target of this GDP was to design a long range flying wing passenger aircraft to meet the increasing global aircraft demand. The name of this flying wing aircraft is FW-11. This is a project cooperated between Aviation Industry Corporation of China (AVIC) and Cranfield University. The writer was involved in the conceptual design stage of this project. The author was in charge of the engine market, engine selection, engine sizing and performance. The target of the IRP is to build a set of health management methods including system real-time monitoring, accurate fault diagnosis and prognosis of major components which are suitable for the aircraft landing gear extension and retraction control system. These technologies have the capability to improve mission reliability of the aircraft and the maintenance costs could be reduced. Simultaneously, aircraft landing gear extension and retraction control system, as one of the most important aircraft systems on-board, could directly affect the flight safety. Consequently, diagnostic, prognostic and health management (DPHM) technology is necessary for the system. Based on the FHA, FMEA and FTA of the aircraft landing gear extension and retraction control system, each of the catastrophic events, all the root causes and their effects were identified. Synchronously, all the components which are related to the catastrophic events were found. The rule-based expert system diagnostic technology was chosen from the available approaches and it was successfully applied on the system. Appropriate prognosis approach was recommended for each component of the system according to the features of components of the system. Finally, the DPHM architecture of the landing gear extension and retraction control system was built.